吉非替尼对肺癌细胞株H358放疗敏感性的影响及其机制 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: The epidermal growth factor receptor (EGFR) is an important determinant of radioresponse, the elevated expression and activity of which frequently correlates with radioresistance in several cancers, including non-small-cell lung carcinoma (NSCLC). The molecular blockade of EGFR signaling is a promising therapeutic strategy for the enhancement of the cytotoxic effects of radiotherapy. The aims of the present study are to observe whether gefitinib, a selective EGFR tyrosine kinase inhibitor, can radiosensitize the NSCLC H358 cell line and to investigate the mechanism by which this drug restores the radiosensitivity of NSCLC cells. METHODS: NSCLC cell line H358 was divided into two groups, namely the X-ray and the gefitinib-interfering groups. The former was irradiated using X-ray only, and the latter was treated with 1 μmol/L gefitinib 24 h before irradiation under the same conditions. The cells were tested using the clonogenic cell survival assay to identify the radiosensitivity of both groups. Immunostaining for confocal microscopy was used to observe nuclear γ-H2AX repair and EGFR foci after irradiation. Nuclear EGFR expression was detected using Western blot after radiotherapy. RESULTS: In the clonogenic cell survival assay, the survival fraction in the gefitinib-interfering group was lower than that in the X-ray group at different doses. Surviving fraction of 2 Gy (SF2) were 0.000, 865 and 0.011, 1 for the gefitinib-interfering and the X-ray groups, respectively. Sensivive enhancement ratio (SER) was 2.815. Immunostaining for confocal microscopy suggested that more nuclear γ-H2AX foci are present in the gefitinib-interfering group than in the X-ray group. The nuclear γ-H2AX foci also stayed longer in the gefitinib-interfering group. EGFR translocated into the nucleus within 1 h in X-ray group, but stayed in the cytoplasma in the gefitinib-interfering group. Western blot was tested using SPSS 13.0, P=0.042. CONCLUSION: Gefitinib, at the cellular level, radiosensitizes EGFR with NSCLC H358 by blocking EGFR nuclear translocation as one of its mechanisms.